Chronic propranolol treatment moderately attenuated development of N-methyl-N-nitrosourea-induced mammary carcinoma in female rats. Issue 10 (November 2021) - Tibensky, Miroslav; Cernackova, Alena; Horvathova, Lubica; Macejova, Dana; Tillinger, Andrej; Mravec, Boris
Abstract : The sympathetic nervous system participates in the development and progression of several cancer types and this effect is mediated mainly via β-adrenergic signaling. However, the potential of β-adrenergic signaling blockade to prevent cancer development after exposure to carcinogens has not been investigated, yet. Therefore, in our study, we determined the effect of the β-blocker propranolol on the development and progression of mammary cancer induced in female rats by administration of the chemical carcinogen N -methyl- N -nitrosourea (MNU). The propranolol treatment (20 mg/kg body weight) started 12 days after MNU administration and lasted 10 weeks. We found that both saline and propranolol treatment significantly increased gene expression of the catecholamine-synthesizing enzyme tyrosine hydroxylase, indicating that repeated injection of saline or propranolol-induced stress in these two groups. However, compared to the vehicle-treated group, propranolol slightly delayed the development and moderately reduced the incidence of mammary carcinoma in animals. To evaluate the mechanisms mediating the effect of propranolol on the development of MNU-induced cancer, we investigated several parameters of the tumor microenvironment and found that propranolol increased gene expression of Casp3. Our data indicate that propranolol treatment that starts after exposure to carcinogens might represent a new, useful approach for preventing the development of cancer, especially in stressed individuals. However, the potential efficiency of propranolol treatment for preventing cancer development and progression in individuals exposed to carcinogens needs further investigation.